(3JbjjOGJ ef hajGJ GHf GdNWjH hJcedI GHf GdbGVis - (3eMeO Hf CMeO Hf YHO Gdedc, CHh YHO Gddg GdaTJGdj(B: (3bGVj aGS,J (B777 (3g` s
(3ChdgG (B:s
(3gPg CHjGJ bjOJgG dfaSi ef hajGJ GHf GdNWjH GdbSfWjfi hRjGOI Ydjg ef JcedI GHf GdbGVi GdecfSi ,hde CYJeO Ydi CUd UMjM s
(3BNQgG (B:s
(3hUd Edg GdYQT ai cd dMXI Ydi SjO GdEQSGd ai cd eMad heGhUd QVGc HGdUHGM hHGdeSG Ydi CdGd hGdCUMGH WQG hCLed s
(3Vef eLehY , JQJjHgG (B: (3ef U (B209 - (3U(B228s
(3efXheIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B286s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B119 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(487(3O(B) s
Keywords: (3GdWHs